Inheritance of pod length and other yield components in two cowpea and yard-long bean crosses - Edematie, V.E.; Fatokun, C.; Boukar, O.; Adetimirin, Victor O.; Kumar, P. Lava (MDPI, 2021)
This study determined the gene effects involved in the inheritance of pod length and other yield-related traits and relationships among traits in crosses between two cowpea lines (TVu 2280 and TVu 2027) and a yard-long bean (TVu 6642) line with long pods. Plants of six generations (P1, P2, F1, F2, BC1P1, and BC1P2) derived from TVu 2280 × TVu 6642 and TVu 2027 × TVu 6642 were evaluated under field conditions. Data collected on 14 yield components of each cross were used for generation mean analysis. Gene effects and their magnitudes varied with the crosses; digenic epistatic gene effects were detected for 10 traits in TVu 2280 × TVu 6642 and 11 traits in TVu 2280 × TVu 6642. Only additive gene effect was significant for pod length in TVu 2280 × TVu 6642 while additive, dominant, and two of the three digenic epistatic gene effects were significant in TVu 2027 × TVu 6642. Models that incorporated only significant additive, dominant, and digenic epistasis were adequate for all 14 traits in TVu 2280 × TVu 6642 and eight of the 12 traits in TVu 2027 × TVu 6642 for which model-fitting was possible. Across segregating generation of the two crosses, pod length (PodLNT) was significantly (p < 0.001) correlated with three major yield components viz. pod weight (0.84, 0.77), number of seeds per pod (0.41, 0.30) and seed weight per pod (0.61, 0.29). Significant correlation of PodLNT with seed yield per plant was moderate and significant (p < 0.01–0.001) in the BC1P1 of the two crosses (0.31 and 0.41). An improvement in cowpea seed yield is feasible through selection for long pods in segregating generations involving crosses with yard-long bean.